Building Special Operations Partnerships in Afghanistan and Beyond Challenges and Best Practices from Afghanistan, Iraq, and Colombia - Long, Austin (Research Reports, 2015)
Building the capacity of Afghan special operations forces (SOF) is a key goal of the United States and its coalition partners. This report summarizes key partnering practices and presents findings from SOF partnership case studies in Afghanistan, Iraq, and Colombia. The goal is to identify best practices to benefit the development of Afghan SOF, as well as for special operations partnerships beyond Afghanistan.